SYNTHESIS AND ANTICANCER ACTIVITY TEST OF 2-HYDROXY-N-PHENYLNICOTINAMIDE - Salahuddin Salahuddin; Muhammad Hanafi; Hariyanti Hariyanti (Universitas Gadjah Mada, 2013)
The novel compound of 2-hydroxy-N-phenylnicotinamide was synthesized from modification of the UK-3A compound, which was known biologically active to inhibit bacterial and cancer cells growth. Synthesis of this compound was carried out in one-step reaction. Analog UK-3A compound namely 2-hydroxy-N-phenylnicotinamide was synthesized from 2-hydroxynicotinic acid as the starting material using amidation reaction with aniline in presence of DCC/DMAP in pyridine. Analog UK-3A was analyzed and identified using TLC, FT-IR, LC-MS and FT-NMR spectrofotometer. The yield after purification was 42.97%. The IC50 value 85 μg/mL was obtained from cytotoxicity test against P388 Murine Leukemia cells. It indicated that the synthesis products were sufficiently potential for leukemia P388 treatment.